(untitled) (Superficies y Vacío, 2017)
Rotary dynamic seals are widely used in machinery in order to retain fluids and to exclude external contaminants by allowing the free shaft movement. One of the most recurrent failure of seals is caused by abrasive wear under prolonged sliding contact. It is mainly produced either by partial dry running (two-body abrasion) and/or by interacting with abrasive hard fine particles, which are immersed in the fluids generating three-body abrasive wear. This work aims to study both types of abrasion using a micro-scale abrasion tester. For this, small samples were extracted from an Acrylonitrile Butadiene Rubber (NBR) lip of an actual dynamic seal. The testing was conducted in dry contact to generate two-body abrasive wear, as well as in a wet/muddy environment in order to reproduce three-body abrasion. The load was selected in order to approach the actual mean contact pressure of seals against rotary shafts. Hence, a stress relaxation test of the NBR samples was carried out to characterize the viscoelastic behavior. The wear scar morphologies and wear progression were analyzed in detail by optical microscopy, SEM analysis and optical profilometry. Finally, the experimental test was suitable to reproduce two-body and three-body abrasion on the samples since the particular wear patterns on small wear scars were obtained by short experiments.